Meningkatkan Kemampuan Berpikir Kritis Pak Dan Bp Dengan Metode PBL Pada Kelas VII SMP Negeri 3 Tebing Tinggi - Rindu Marito Sinaga; Ansel Joko Prayitno (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
This article is a literature review which aims to provide a study of the Problem Based Learning (PBL) learning model to improve critical thinking skills. In this article we will discuss the PBL learning model and critical thinking skills as well as the relationship between PBL and critical thinking skills. PBL is learning obtained through a process towards understanding the resolution of a problem, through PBL students gain experience in dealing with realistic problems, and emphasizes the use of communication, cooperation and existing resources to formulate ideas and develop reasoning skills. Critical thinking skills can be interpreted as high-level thinking skills, which are a deliberate and conscious process of interpreting and evaluating information from existing experiences, beliefs and abilities with the aim of testing an opinion or idea, including making considerations or thoughts based on the opinions put forward. Ennis in Costa (1985) developed indicators of critical thinking skills, consisting of: (1) Elementary clarification (providing a simple explanation), (2) Basic support (building basic skills), (3) Inference (concluding), (4) Advances clarification (making further explanations), and (5) Strategies and tactics (strategy and tactics). Critical thinking skills can be improved through PBL because the learning approach is based on authentic problems, and students are not only asked to understand a problem but also have to be able to work together to solve the problem, so that it can stimulate students' abilities and skills, especially critical thinking skills.